Minerales espaciales: cosas de nadie en beneficio de todos - Marinho Amorim, Hellen (2019)
The exploitation of terrestrial mineral resources has been a source of economic benefits, environmental damage and human costs. New technologies, however, have been promoting space mining with the potential of synchronizing the benefits of this economic activity and reducing social and environmental damages. In this perspective, the present study examines two legal implications of this technological innovation: the legal nature and the ownership of natural space resources. With the objective of recognizing the most plausible legal subject, according to legal, logical and ethical criteria, in order to obtain title to the right of ownership of space ores and to propose the most appropriate treatment for their profits, the approach adopted aims to link land and space mining based on the perspective of renewed continuity. In order to reach this theoretical proposition, were previously analyzed the human and environmental impacts of terrestrial mining; the feasibility of using and exploiting space ores, as well as the advantages and disadvantages of space mining; and both the political and normative positions —international and local— and the academic-doctrinal positions —negationists, expansionists and analogists—about this property right. It is concluded that space ores are best classified as res nullius, appropriable by any persons, physical or legal, public or private, as long as they commit to certain requirements as to their profits, which culminates in a reasonable proposal of regulation for mining, which is both feasible and beneficial to mankind and the environment.